'Core Maths chooses you; you don't choose Core Maths'. The positioning of a new mathematics course within the post‐16 curriculum in England. Issue 4 (4th February 2020) - Mathieson, Rachel; Homer, Matt; Tasara, Innocent; Banner, Indira
Abstract: A recent government move to increase numbers of students taking post‐16 (post‐compulsory) mathematics in England saw 2930 students being awarded the first Core Maths (CM) qualifications in 2016, the number rising to 9027 in 2019. This paper uses qualitative data, from a study investigating the successes and challenges of these new qualifications in their initial period of implementation, to explore perspectives on how the new qualification is being positioned within the existing post‐16 curriculum structure. First‐ and second‐order effects of the policy are considered, particularly in relation to the dichotomy between CM and the longstanding, highly academic, A‐level Mathematics. Our findings reveal a positive regard for many aspects of CM. However, the systemic processes by which certain students are manoeuvred onto the CM course, and the resulting opportunities for progression of those students, could be interpreted as restrictive, despite the benefits for students of new opportunities for pursuing mathematics study.